Physiological responses and performance during a 3-minute cycle time trial: standard paced versus all-out paced - Dobler, F.; Bachl, P.; Stöggl, T.; Andersson, E. P. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To compare performance and physiological responses between a standard-paced 3-minute time trial (TTSP, ie, pacing based on normal intention) and a consistently all-out-paced 3-minute time trial (TTAOP).